2021
DOI: 10.1002/capr.12429
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of group cognitive behavioural therapy in improving adaptive cognitive emotion regulation in Nigerian breast cancer patients

Abstract: Globally, breast cancer is the most common form of cancer among women (Carayol et al., 2012;Morgan, 2018) particularly in low-and middle-income countries (LMICs) such as Nigeria (Abiodun Olatunde et al., 2012;Afolayan et al., 2012). Most women with a breast cancer diagnosis frequently develop psychopathological disturbances during medical treatment (de Caralho et al., 2015;Kissane et al., 2004) or during follow-up (Celik et al., 2016). After treatment, most women are especially weighed down by threat of death,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…22 CBT was discovered to be a significantly useful intervention for treating depression among Nigerian breast cancer patients. 24 Despite the effectiveness of psychoeducation in treating depression, Onyedibe et al 23 revealed that no difference was found between breast cancer patients who underwent psychoeducation intervention and those in the control group.…”
Section: Psychological Interventions For Treating Depression Associat...mentioning
confidence: 99%
See 3 more Smart Citations
“…22 CBT was discovered to be a significantly useful intervention for treating depression among Nigerian breast cancer patients. 24 Despite the effectiveness of psychoeducation in treating depression, Onyedibe et al 23 revealed that no difference was found between breast cancer patients who underwent psychoeducation intervention and those in the control group.…”
Section: Psychological Interventions For Treating Depression Associat...mentioning
confidence: 99%
“…The table includes 5 studies that were analyzed. [20][21][22][23][24] The minimum sample size of breast cancer patients was 13 20 , while the maximum sample size was 38. 23 Research on psychological interventions for treating depression in breast cancer patients in Nigeria began in 2015 20 , with the most recent research published in 2022.…”
Section: Psychological Interventions For Treating Depression Associat...mentioning
confidence: 99%
See 2 more Smart Citations
“…According to the findings of a recent study (Onyedibe, Ifeagwazi & Charles, 2021), which focused on the efficacy of group cognitive behavioral therapy for emotional regulation in women with breast cancer, the relationship between adaptive and maladaptive strategies of emotional regulation shifted in favor of the latter after the implementation of a 12-week intervention program. Another paper (Qiu, Chen, & Gao, 2013) reported that cognitive behavioral therapy can be successfully used to treat depression, as well as to improve the overall quality of life and self-esteem in breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%